Simulated Interprofessional Education Discharge Planning Meeting to Improve Skills Necessary for Effective Interprofessional Practice. Issue 2 (March 2018) - Smith, Leslie M.; Keiser, Megan; Turkelson, Carman; Yorke, Amy M.; Sachs, Benjamin; Berg, Karen
Abstract : Purpose of Study: The purpose of this study was to evaluate the use of a simulation-enhanced interprofessional education (Sim-IPE) discharge planning learning experience using simulated patients (SPs), to explore the ability for students to communicate with each other and to a patient/caregiver, and to use clinical thinking to make a safe and appropriate interprofessional discharge recommendation. Primary Practice Setting(s): Educational institution; university simulation center. Methodology and Sample: A Sim-IPE was performed with students from physical therapy ( N = 46), nursing ( N = 25), and social work ( N = 11). Students were placed into interprofessional teams. Presimulation, each student was expected to complete a survey and review several items including the patient case, a communication strategy, and community resources. The team then interacted with SPs portraying the patient and the family member. Postsimulation, facilitators led a debriefing session and students completed a post-IPE survey. The Interprofessional Collaborative Competency Attainment Survey (ICCAS) was completed pre- and postexperience. Results: Most students reported that they strongly or somewhat agreed that the experience improved their clinical thinking skills (67%; n = 55), improved awareness of the patient voice in shared decision-making (72.8%; n = 59), improved ability to prioritize patient's list of impairments (75.3%; n = 61), and improved confidence with discharge planning (69.1%; n = 56). Implications for Case Management Practice: Discharge planning is inherently an interprofessional process. Utilizing a simulation as a method to practice discharge planning may have a positive impact on future clinical practice. Completing the ICCAS may not be the appropriate assessment when evaluating change before and after an IPE experience based on the high scores noted preexperience. The use of a simulated discharge planning meeting may improve skills necessary for effective interprofessional practice.